2015
DOI: 10.4081/hpr.2015.2244
|View full text |Cite
|
Sign up to set email alerts
|

Parental perceptions of health-related quality of life of Albanian children with epilepsy

Abstract: Epilepsy adversely affects the health-related quality of life (HRQoL) of children living with it. Even though almost 80% of children with epilepsy live in developing countries very little research has been conducted with the specific population. The present study took place in Albania and aimed to investigate parental perceptions of the HRQoL of their children with epilepsy. Considering the well-defined gender roles in the Albanian traditional family it was expected that mothers and fathers reports of their ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
(21 reference statements)
3
3
0
Order By: Relevance
“…This can be explained by the fact that more than two-thirds of cases were disclosure the diagnosis over a year ago (at the time of the study), and according to the adaptation theory, the negative feelings and caregiving burden declines over time due to the development of new adaptation capacities [30]. The gender of the children' guardian was not significant in present study and it was consistent with other studies [19] [31] [32]. In Malaysia, the women were the main caregiver in providing care during child sickness.…”
Section: Discussionsupporting
confidence: 88%
“…This can be explained by the fact that more than two-thirds of cases were disclosure the diagnosis over a year ago (at the time of the study), and according to the adaptation theory, the negative feelings and caregiving burden declines over time due to the development of new adaptation capacities [30]. The gender of the children' guardian was not significant in present study and it was consistent with other studies [19] [31] [32]. In Malaysia, the women were the main caregiver in providing care during child sickness.…”
Section: Discussionsupporting
confidence: 88%
“…These high mother-father agreements are in line with current research, that reported moderate to strong agreements [35, 37, 50, 5759]. But while most studies investigated internalizing and externalizing behavior, only two studies are available, that focused on inter-parental agreement of parent-reported child HRQOL [56, 60]. These samples consisted of parents of children with mental disorders in a clinical setting or parents of healthy children.…”
Section: Discussionsupporting
confidence: 83%
“…These samples consisted of parents of children with mental disorders in a clinical setting or parents of healthy children. Only one study included parents of chronically ill children [60].…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, we wanted to identify differences between mothers and fathers in their assessment of their children’s HRQoL. Previously, only a few studies investigated parent-reported child HRQoL [ 26 28 ]. However, parent-reported HRQoL of early childhood cancer survivors has not been examined before.…”
Section: Discussionmentioning
confidence: 99%